EFFECTIVENESS OF THE LAW IN THE MINUTE CRIME OF PALM OIL THEFT - Jufri; Indra Afrita; Sandra Dewi (JILPR Journal Indonesia Law and Policy Review, 2026)
This study aims to analyze the effectiveness of the law in handling the minor crime of palm oil theft in the jurisdiction of the Pasir Penyu Police, identify obstacles faced by law enforcement officers in enforcing the law against this crime, and examine efforts made to improve the effectiveness of law enforcement. The crime of palm oil theft is a form of crime that often occurs in plantation areas and causes economic losses for the community and companies. Although some cases are classified as minor crimes, their handling must still pay attention to legal certainty, justice, and legal benefits. The research method used is sociological (empirical) legal research with a descriptive nature. Primary data was obtained through interviews with the Pasir Penyu Police Chief, investigators, Bhabinkamtibmas, plantation company officials, and the community, while secondary data was obtained through a literature study consisting of primary, secondary, and tertiary legal materials. Data analysis was conducted qualitatively by drawing conclusions deductively. The results of the study indicate that the effectiveness of the law in handling the minor crime of palm oil theft in the jurisdiction of the Pasir Penyu Police has not been running optimally. Law enforcement has been implemented in accordance with the provisions of the Criminal Code and the Criminal Procedure Code, but its effectiveness is still influenced by various factors, including low public legal awareness, the perpetrators' economic factors, the vast plantation areas that are difficult to monitor, limited police personnel, and the continued tendency to resolve cases through a familial approach. These obstacles have led to the recurrence of palm oil theft crimes. Efforts made by the Pasir Penyu Police include increasing patrols in plantation areas, coordinating with companies and village governments, providing legal counseling to the community, optimizing the function of Bhabinkamtibmas, and professional law enforcement against each perpetrator in accordance with statutory provisions. Based on the results of the study, it can be concluded that the effectiveness of the law in handling minor crimes of palm oil theft in the jurisdiction of the Pasir Penyu Police has not been fully achieved because there are still various factors that hinder law enforcement. Therefore, synergy is needed between law enforcement officers, plantation companies, local governments, and the community to improve legal compliance and prevent the occurrence of palm oil theft crimes on an ongoing basis.